The Development of the Current Da'wah Model through the Diagnosis Counseling Technique of the 10 Big Sins - Khilman Rofi Azmi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2019)
The dynamics and needs of the Islamic community are developing by the demands of the times. This article aims to create an alternative model of da'wah to answer the needs of the Islamic community, especially for the millennial generation. The da'wah model is practical and focuses on solving problems through the diagnosis of 10 significant sins which including Syirik, Leave the Sholat, Disobedience to parents, Adultery, Eating illegitimate or Haram (assets of orphans), Drinking Khamr, Deciding of Silaturahm (Moslem Relationship), Fake Oaths, Miser; and Slandering. The present model of da'wah through the diagnosis technique of 10 major sins is designed by integrating the